Developing Practice for Public Health and Health Promotion - Naidoo, Jennie; Wills, Jane, MSc. (London : Baillière Tindall, 2010)
This text helps practitioners clarify for themselves the scope, direction and skills embodied within health promotion and public health practice.
Includes bibliographical references and index.
Keywords: Health promotion -- Great Britain; Health behavior -- Great Britain; Health education -- Great Britain